2003
DOI: 10.1002/jcp.10293
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of stem cells in the central nervous system

Abstract: Injury to the central nervous system (CNS) can result in severe functional impairment. The brain and spinal cord, which constitute the CNS, have been viewed for decades as having a very limited capacity for regeneration. However, over the last several years, the body of evidence supporting the concept of regeneration and continuous renewal of neurons in specific regions of the CNS has increased. This evidence has significantly altered our perception of the CNS and has offered new hope for possible cell therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 121 publications
(137 reference statements)
1
10
0
2
Order By: Relevance
“…Recently, it has become clear that the determined stem cell is in fact Stem cells are defined by their capacity for selfrenewal and differentiation into different cell types (87, phenotypically plastic and is able to give rise to cells from different germ layers, a process known as transdif-89,94). In the early embryonic phase, stem cells are totipotent but after a few divisions the cells are determined ferentation (10, 45,66,67,71). Because of their versatility, stem cells have gained to become specific for one of the three germ layers: the ectodermal layer, which will give rise to skin and neural ample attention over the last years for their potential in replacement/repair approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has become clear that the determined stem cell is in fact Stem cells are defined by their capacity for selfrenewal and differentiation into different cell types (87, phenotypically plastic and is able to give rise to cells from different germ layers, a process known as transdif-89,94). In the early embryonic phase, stem cells are totipotent but after a few divisions the cells are determined ferentation (10, 45,66,67,71). Because of their versatility, stem cells have gained to become specific for one of the three germ layers: the ectodermal layer, which will give rise to skin and neural ample attention over the last years for their potential in replacement/repair approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, regenerative approaches using stem cells have focused more on adult stem cells. Adult stem cells have been found in a variety of tissues such as bone marrow, skeletal muscle [20], adipose [21], central nervous system [22], lung, and inner ear [23]. These cells can be targeted in their native environment or isolated, manipulated ex vivo, and transplanted.…”
Section: Cell-based Therapymentioning
confidence: 99%
“…As the cell mass develops, the daughter cells begin to acquire properties different from one another, so that different regions destined to become different components of the embryo are formed. Recently, it has been suggested that the determined stem cell is in fact phenotypically plastic and is able to give rise to cells from different germ layers, a process known as transdifferentiation (Morrison et al, 1997;Johansson et al, 2003). The process of transdifferentiation can also result in the formation of abnormal phenotypes having no counterpart in the normal body (dysplasia).…”
Section: Determinationmentioning
confidence: 99%